2017
DOI: 10.3390/ijms18102066
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Super-Resolution Localization Microscopy and Biomolecular Fluorescent Nano-Probing in Cancer Research

Abstract: Understanding molecular interactions and regulatory mechanisms in tumor initiation, progression, and treatment response are key requirements towards advanced cancer diagnosis and novel treatment procedures in personalized medicine. Beyond decoding the gene expression, malfunctioning and cancer-related epigenetic pathways, investigations of the spatial receptor arrangements in membranes and genome organization in cell nuclei, on the nano-scale, contribute to elucidating complex molecular mechanisms in cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(93 citation statements)
references
References 80 publications
0
93
0
Order By: Relevance
“…Researchers have considered the impacts of low-dose radiation, given as a single dose or fractionated or prolonged over time, with regard to altering cancer progression or resolution as well as their impacts on the systemic immune system [23] .It was found that low-dose radiation increases cellular antioxidant activity; facilitates DNA damage repair; reduces malignant transformation and mutagenesis, and stimulates immune surveillance [24]. The cell nucleus and DNA are susceptible to several stressors[25, 26,27,28] and can be greatly harmed with relatively low doses of ionizing radiation [29,30]. As adverse effects of ionizing radiation on (cancer) cells are mainly mediated by fragmentation of nuclear chromatin via inserting double strand breaks (DSBs) into the DNA molecule [31].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have considered the impacts of low-dose radiation, given as a single dose or fractionated or prolonged over time, with regard to altering cancer progression or resolution as well as their impacts on the systemic immune system [23] .It was found that low-dose radiation increases cellular antioxidant activity; facilitates DNA damage repair; reduces malignant transformation and mutagenesis, and stimulates immune surveillance [24]. The cell nucleus and DNA are susceptible to several stressors[25, 26,27,28] and can be greatly harmed with relatively low doses of ionizing radiation [29,30]. As adverse effects of ionizing radiation on (cancer) cells are mainly mediated by fragmentation of nuclear chromatin via inserting double strand breaks (DSBs) into the DNA molecule [31].…”
Section: Discussionmentioning
confidence: 99%
“…For each series of SMLM experiments, typically 50 cell nuclei were registered. An in-house software (see [31,39,54,65,77,78] for detailed descriptions) was used for the localization of signal points from blinking events in raw image stacks. The resulting data matrix containing the coordinates of detected signals was subject to further computational analysis.…”
Section: Localization Microscopymentioning
confidence: 99%
“…Thereby, mega base-pair sized topologically associating domains (TADs) and subdomains therein (subTADs) [26][27][28][29] have been identified as structural units of the threedimensional genome [30]. In parallel, modern super-resolution microscopy technologies [31][32][33][34][35][36][37][38][39] have been developed, enabling analyses at the single cell level of cellular nanostructures and molecular interactions on the order of magnitude of single antibodies, histones, receptors, etc. (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations